Contextualizing Hypertension and Its Treatment Seeking Among Slum Dwellers in Mumbai, India. Issue 2 (July 2019) - Pradhan, Manas Ranjan; Bolleddu, S. B.
Abstract: Sizable Indians suffer from hypertension, and this number is multiplying. There is, however, a shortage of information about lay perception of hypertension and its management—especially among the socio-economically disadvantaged urban population. This study using grounded theory approach explores the explanatory models held by the socio-economically disadvantaged urban communities on hypertension and its management. The results are based on six key informant interviews, three focus group discussions and 21 in-depth interviews from a slum in Mumbai, India. Consent was sought from each participant. ATLAS.ti software was used for analysis. The relationship among emerging themes, categories, and codes were studied using memos and network analysis through an iterative process. The study documents inadequate and varied understanding of hypertension (generally referred to as BP) and its risk factors. The commonly reported perceived risk factors for hypertension were improper food habits, alcohol use, family issues, financial problems, physical inactivity, and unplanned urbanization. Perceived understanding of the risk factors and consequences led to varied pathways of management of hypertension. Hypertension awareness programs and mass screening are pertinent to reduce disease burden and better health outcome of the urban socio-economically disadvantaged populations.